MEMBANGUN KOMUNIKASI ANTARA GURU DAN SISWA GUNA MENANGANI PERILAKU SISWA YANG BERMASALAH DI KELAS - Lestari, Sudarsri; Sholekah, Salmahtus (Jurnal Pena Karakter (Jurnal Pendidikan Anak dan Karakter), 2019)
Communication is also an important thing that must be owned by the teacher. In delivering teaching material to students, a teacher who has good communication skills can encourage students to be able to absorb lessons well and the smooth learning process can achieve maximum results. Communication between teacher students who do not work well can cause problems in class. One of them is the behavior of problematic students in the classroom that can disturb the concentration of other students in absorbing lessons. The main characteristic of SD/MI students is to display many individual differences, including, differences in intelligence, cognitive and language abilities, personality development and physical development. Differences between individuals in SD/MI students that ultimately can give birth to diversity of behavior. Teachers need to master good communication in order to be able to control the behavior of students in the classroom. To realize good communication skills, there are three steps that need to be done, namely knowing, learning, and applying the three main aspects of communication. The three aspects of communication include speaking skills, listening skills, and non verbal skills.